2019
DOI: 10.3389/fpls.2019.00262
|View full text |Cite
|
Sign up to set email alerts
|

A Stimulatory Role for Cytokinin in the Arbuscular Mycorrhizal Symbiosis of Pea

Abstract: The arbuscular mycorrhizal (AM) symbiosis between terrestrial plants and AM fungi is regulated by plant hormones. For most of these, a role has been clearly assigned in this mutualistic interaction; however, there are still contradictory reports for cytokinin (CK). Here, pea plants, the wild type (WT) cv. Sparkle and its mutant E151 (Pssym15), were inoculated with the AM fungus Rhizophagus irregularis. E151 has previously been characterized as possessing high CK levels in non-mycorrhizal (myc-) roots and exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
(124 reference statements)
0
14
0
Order By: Relevance
“…We noted that, recently, there are contrasting reports on the efficacy of INCYDE in response to biotic and abiotic stressors [ 34 , 51 , 59 ], as well as reports showing both enhanced [ 54 , 55 ] and decreased content of cytokinins [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that, recently, there are contrasting reports on the efficacy of INCYDE in response to biotic and abiotic stressors [ 34 , 51 , 59 ], as well as reports showing both enhanced [ 54 , 55 ] and decreased content of cytokinins [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has also shown contradictory effects of INCYDE. INCYDE decreased the content of cytokinins in non-mycorrhizal control pea plants, particularly the nucleotide forms [ 58 ], while in Arabidopsis subjected to heat stress, F-INCYDE (a fluorinated analog of INCYDE, 2-fluoro-6-(3-methoxyphenyl)aminopurine [ 19 ]) exacerbated negative stress effects and delayed the stress response of non-acclimated plants [ 59 ]. A decrease in cytokinin nucleotide forms was also detected.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of pathogen resistance promoted by CK has been shown in several plant–pathogen systems, which seems to be synergistic with, and dependent on, SA‐responsive pathways (Choi et al ., 2010 ; Jiang et al ., 2013 ; Reusche et al ., 2013 ). Contrastingly, CK appears to support the progression of fungal biotrophic pathogens and stimulate beneficial AMF interactions in pea ( Pisum sativum ) (Walters and McRoberts, 2006 ; Chanclud et al ., 2016 ; Morrison et al ., 2017 ; Goh et al ., 2019 ).…”
Section: Plant Hormone Excretion and Signalling Can Shape The Rhizosphere Microbiomementioning
confidence: 99%
“…Plants co‐exist with microorganisms in nature, and plant growth‐promoting microbiomes help plants resist stress via CTKs (Egamberdieva et al, 2017; Goh et al, 2019; Jorge et al, 2019). As CTKs are interkingdom signalling molecules, investigations into the possible function of IPTs , and how bacteria and fungi enhance plant stress resistance would increase our understanding of these beneficial interactions and could also provide novel technologies for crop stress management.…”
Section: Concluding Remarks and Future Stepsmentioning
confidence: 99%